2022
DOI: 10.3389/fmats.2021.802379
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Conductivity Correlation in NASICON Based Na3Al2P3O12 Glass: Effect of Na2SO4

Abstract: Identifying the factors influencing the movement of sodium cations (Na+) in glasses accelerates the possible options of glass-based solid electrolyte materials for their applications as a promising electrolyte material in sodium-ion batteries. Nevertheless, due to the poor correlation between the structure and conductivity in glass materials, identifying the factors governing the conductivity still exists as a challenging task. Herein, we have investigated the DC-conductivity variations by correlating the stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…This clearly indicates that Na 2 SO 4 has a positive impact on conductivity for concentration >5 mol %. Several studies in the literature have reported that the addition of Na 2 SO 4 in phosphate glasses enhances the conductivity value. , Na 2 SO 4 decomposed in a glass structure and formed isolated SO 4 2– anions and Na + cations. Additionally, these large SO 4 2– anions accumulated in the channel regions surrounded by Na + cations.…”
Section: Resultsmentioning
confidence: 99%
“…This clearly indicates that Na 2 SO 4 has a positive impact on conductivity for concentration >5 mol %. Several studies in the literature have reported that the addition of Na 2 SO 4 in phosphate glasses enhances the conductivity value. , Na 2 SO 4 decomposed in a glass structure and formed isolated SO 4 2– anions and Na + cations. Additionally, these large SO 4 2– anions accumulated in the channel regions surrounded by Na + cations.…”
Section: Resultsmentioning
confidence: 99%
“…Even at 10 A g −1 , its capacity still reaches 321 mAh g −1 . According to the simulation results, the amorphous Fe 2 O 3 has a much lower intercalation energy of 1.82 eV compared with crystal Fe 2 O 3 [111] Copyright 2022, Frontiers Media S.A. b) Structure of pure NaPO 3 , 80NaPO 3 -20AlF 3 , and 60NaPO 3 -40AlF 3 glasses. Reproduced with permission.…”
Section: Non-glass Ams For Sodium Batteriesmentioning
confidence: 96%
“…The DC‐conductivity change in Na 3 Al 2 P 3 O 12 (Na 2 O‐Al 2 O 3 ‐P 2 O 5 ) glass caused by substituting Na 2 SO 4 for Al 2 O 3 was measured to identify the factors influencing the ionic conductivity. [ 111 ] Raman spectroscopy results show that increasing the Na 2 SO 4 content can increase the fraction of isolated SO 4 2− units, which are charge compensated by sodium‐ion ( Figure a). Magic‐angle spinning (MAS)‐NMR results further indicate that increasing the Na 2 SO 4 content also increases the content of nonbridging oxygens.…”
Section: Am‐based Batteriesmentioning
confidence: 99%
See 2 more Smart Citations